Differences in dementia prevention knowledge by educational attainment: an analysis of a household survey from Great Britain - Emilie Courtin; Sarah Eley (BMJ Public Health)
Background Higher levels of education are associated with slower cognitive decline and a lower risk of dementia, with some evidence of a causal relationship. However, the mechanisms explaining these associations are not well established.Methods We collected data on dementia knowledge using a cross-sectional household survey representative of the population of Great Britain. Dementia knowledge was assessed using a self-reported measure and a question measuring the knowledge of key risk factors. We examined whether dementia knowledge varied by levels of education (as measured by the level of the highest qualification) by fitting logistic regressions adjusted for confounding factors.Findings Out of the 5036 respondents aged 25 or over (46.6% male; average age 63.8), 9.3% reported knowing a great deal about dementia, and 32.2% quite a lot. We found a strong educational gradient in dementia prevention knowledge. For people with a degree qualification compared with people with no formal qualification, the ORs of reporting having quite a lot or a great deal of knowledge about dementia were 2.54 (95% CIs 1.81 to 3.56). The ORs were 3.58 (2.61 to 4.91) for mentioning all risk factors. The difference in awareness by educational level was largest for some risk factors such as lack of physical and mental activity, alcohol consumption and poor mental health.Interpretation The protective effect of higher levels of education against the risk of dementia may partly be driven by differences in dementia prevention knowledge. Health education efforts on dementia prevention should target people with lower levels of education to reduce inequalities in dementia prevalence.